Symptomatic macroglossia and tongue myositis in Dermatomyositis - Ajili Faida; Bousseta Najeh; Msakni Issam; Metoui Leila; Gharsallah Imen; Laabidi Janet; Ben Abdelhafidh Nadia; Louzir Bassem; Ammar Bouziani; Othmani Salah (Our Dermatology Online, 2013)
The involvement of the tongue in dermatomyositis is rarely described in the literature. We report the case of a patient having a macroglossia whose etiologic was a dermatomyositis. The diagnosis was established by biopsy of the tongue which showed an interstitial lymphocytic infiltration associated with destruction of muscle fibers and perifascicular atrophy. The treatment was based on corticosteroids. The functional prognosis was dominated by the gene to speech and the swallowing disorders.